(untitled) - Ritter, John H.; 1951- (New York, 2003)
The fate of a small California town rests on the outcome of one baseball game, and Tom Gallagher hopes to lead his team to victory with the secrets of the now disgraced player, Dante Del Gato.
Keywords: Baseball; Fiction; California; Fiction